(untitled) (Avocetta, 2024)
The urban populations of Woodpigeon (Columba palumbus) is increasing throughout Europe, generating conflicts with humans associated with damage resulting from their feces deposition or with their role in the maintenance of zoonotic diseases. Despite this, the species has a significant conservation value, as it is an important part of the diet of various threatened raptors like the Bonelli´s (Aquila fasciata) and Iberian Imperial Eagle (Aquila adalberti). Also, it is a game species whose hunting generates large income in certain regions. In the present work, we assessed the habitat selection during the nesting period, analyzing the tree species used for nesting and nest distribution patterns in streets and urban parks. It has been verified how the location of the nest is not random, with a percentage of them in evergreen trees significantly higher than expected and with a significant selection of certain tree species like Pinus sp., Robinia pseudoacacia or Ulmus sp …) while others like Prunus sp., Melia azedarach or Populus sp were avoided. Significant differences were also found in the density of nests, being significantly greater in the streets (12.3 ±11.6 nest/ha) than in parks (5.7 ±3.7 nest/ha). It is discussed how the plantations in areas with benches or vehicle parking of tree species negatively selected by Woodpigeons for nesting and tree species positively selected by Woodpigeons in the rest of the park areas might lead to a reduction of the species associated conflicts while guaranteeing its conservation.